2020
DOI: 10.3311/ppci.16389
|View full text |Cite
|
Sign up to set email alerts
|

Prof. Comparing H2 and H∞ Algorithms for Optimum Design of Tuned Mass Dampers under Near-Fault and Far-Fault Earthquake Motions

Abstract: In this study, the robust optimum design of Tuned Mass Damper (TMD) is established. The H2 and H∞ norm of roof displacement transfer function are implemented and compared as the objective functions under Near-Fault (NF) and Far-Fault (FF) earthquake motions. Additionally, the consequences of different characteristics of NF ground motions such as forward-directivity and fling-step are investigated on the behavior of a benchmark 10-story controlled structure. The Colliding Bodies Optimization (CBO) is employed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The optimum design of TMDs have been at the center of different researchers' interest since its introduction in the literature. Although many different analytical, quasi-analytical and even heuristic methods have been implemented for optimum design of a TMD, the metaheuristic algorithms are the only well-appreciated methods to find the optimum values of design parameters for a multi-degree-of-freedom (MDOF) building with inherent damping [22][23][24][25]. Nevertheless, for ICDTMD, the number of design variables (frequency and damping ratios for the two TMDs) is doubled, and an appropriate metaheuristic algorithm should be selected for the complex optimization problem.…”
Section: Optimum Design Of the Control Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimum design of TMDs have been at the center of different researchers' interest since its introduction in the literature. Although many different analytical, quasi-analytical and even heuristic methods have been implemented for optimum design of a TMD, the metaheuristic algorithms are the only well-appreciated methods to find the optimum values of design parameters for a multi-degree-of-freedom (MDOF) building with inherent damping [22][23][24][25]. Nevertheless, for ICDTMD, the number of design variables (frequency and damping ratios for the two TMDs) is doubled, and an appropriate metaheuristic algorithm should be selected for the complex optimization problem.…”
Section: Optimum Design Of the Control Devicesmentioning
confidence: 99%
“…The gradient-based optimization methods have been used by numerous researchers for optimal design of TMDs [30][31][32][33]. Yang et al [29] reported that gradient-based optimization methods can accurately determine local optimum points, while to find global optimums researchers have used the global optimization methods, such as PSO [14], Charged System Search (CSS) [1,24], Colliding Bodies Optimization (CBO) [16,25], Genetic Algorithm (GA) [34], Simulated Annealing (SA) [35], among others. However, the focus of this paper is on the performance evaluation of a newly proposed tandem based TMDI.…”
Section: Optimum Design Of the Control Devicesmentioning
confidence: 99%
“…In some investigations, the maximum amplitude of the transfer function of the structure is selected as an objective function. The teaching learning-based optimization (TLBO), flower pollination algorithm (FPA), harmony search (HS) [13], and colliding bodies optimization (CBO) algorithm [21] were applied to determine optimum parameters of the TMD system for fixed base structures.…”
Section: Introductionmentioning
confidence: 99%
“…The branch of structural optimization has been extensively developed in the last three decades and could be classified as follows: (1) obtaining optimal size of structural members (size optimization); (2) finding the optimal form for the structure (shape optimization); and (3) achieving optimal size and connectivity between structural members (topology optimization). Metaheuristic algorithms have been widely used in the field of structural optimization [16][17][18][19][20][21][22]. Most of the studies focused on the size optimization of structures that its purpose is to design structures with minimum weight or to minimize a target function corresponding to the minimal cost of construction while the design constraints are met simultaneously.…”
Section: Introductionmentioning
confidence: 99%